Trigenic neural crest-restricted Smad7 over-expression results in congenital craniofacial and cardiovascular defects - Tang, Sunyong (2010)
Smad7 is a negative regulator of TGFβ superfamily signaling. Using a three-component triple transgenic system, expression of the inhibitory Smad7 was induced via doxycycline within the NCC lineages at pre- and post-migratory stages. Consistent with its role in negatively regulating both TGFβ and BMP signaling in vitro, induction of Smad7 within the NCC significantly suppressed phosphorylation levels of both Smad1/5/8 and Smad2/3 in vivo, resulting in subsequent loss of NCC-derived craniofacial, pharyngeal and cardiac OFT cushion cells. At the cellular level, increased cell death was observed in pharyngeal arches. However, cell proliferation and NCC-derived smooth muscle differentiation were unaltered. NCC lineage mapping demonstrated that cardiac NCC emigration and initial migration were not affected, but subsequent colonization of the OFT was significantly reduced. Induction of Smad7 in post-migratory NCC resulted in interventricular septal chamber septation defects, suggesting that TGFβ superfamily signaling is also essential for cardiac NCC at post-migratory stages to govern normal cardiac development. Taken together, the data illustrate that tightly regulated TGFβ superfamily signaling plays an essential role during craniofacial and cardiac NCC colonization and cell survival in vivo.